Comparison of isotope analysis and tank model calculation method to determine the snowmelt water ratio in river water. (2017) - Harada, Shigeki; Hashimoto, Taisuke; Sato, Taisuke
Isotope analysis of river water can be used to evaluate the contribution of snowmelt water in rivers because snow (precipitation) has relatively higher δ 18 O-NO3 . Quantitative determination of snowmelt water input is needed for catchment environmental planning, agricultural planning and water resources planning in heavy snow regions, such as Miyagi Prefecture in Tohoku, Japan. We compared the measured δ 18 O-NO3 values in the Okura River (Sendai, Miyagi Prefecture) in the snowmelt seasons of 2013 and 2014 with the snowmelt water ratio calculated by the tank model for the years 1985 to 1989 and reported in Kato and Kurashima (1998). Although the seasonal periods of δ 18 O-NO3 measurements were not identical with the earlier period, with consideration of the meteorological conditions, variation in δ 18 O-NO3 was well explained by the contribution of snowmelt water to the river determined by the tank model. Thus, measured δ 18 O-NO3 could be used for catchment environmental planning in the region. This case study demonstrates the potential use of δ 18 O-NO3 values for determining the snowmelt water ratio in other rivers.